Trends in anthropogenic ammonia emissions in China since 1980: A review of approaches and estimations - Chen, Jianan; Cheng, Miaomiao; Krol, Maarten; de Vries, Wim; Zhu, Qichao; Liu, Xuejun; Zhang, Fusuo; Xu, Wen (Frontiers in Environmental Science, 2023)
Ammonia (NH3) emissions from intensive anthropogenic activities is an important component in the global nitrogen cycle that has triggered large negative impacts on air quality and ecosystems worldwide. An accurate spatially explicit high resolution NH3 emission inventory is essential for modeling atmospheric aerosol pollution and nitrogen deposition. However, existing NH3 emission inventories in China are still subject to several uncertainties. In this review we firstly summarize the widely used methods for the estimate of NH3 emissions and discuss their advantages and major limitations. Secondly, we present aggregated data from ten NH3 emission inventories to assess the trends in total anthropogenic NH3 emissions in China over the period 1980-2019. The results reveal a noticeable variation of the total ammonia emission estimates for China among selected datasets. In 2010, the median emission (Tg yr-1) and associated ranges were 11 (8.5_14.2) for total emission, 9.6 (8.1_11.4) for agriculture, 0.3 (0.2_1.0) for industry, 0.4 (0.2_0.9) for residential and 0.1 (0.03_0.3) for transport, biomass burning and waste disposal present major sources as other emission of 1.4 (0.2_2.2). The uncertainty analysis shows that the ranges of difference in annual NH3 emissions between the ten models for a given year was as large as the median value for that year. Finally, we made an analysis of the sources and levels of uncertainty in NH3 emission estimates with recommendations for improvement of China’s NH3 emission inventory